2010
DOI: 10.1007/s12601-010-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Conjunction of 2D and 3D modified flow solvers for simulating spatio-temporal wind induced hydrodynamics in the Caspian Sea

Abstract: The main objective of this study is the simulation of flow dynamics in the deep parts of the Caspian Sea, in which the southern and middle deep regions are surrounded by considerable areas of shallow zones. To simulate spatio-temporal wind induced hydrodynamics in deep waters, a conjunctive numerical model consisting of a 2D depth average model and a 3D pseudo compressible model is proposed. The 2D model is applied to determine time dependent free surface oscillations as well as the surface velocity patterns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…The results obtained in this research were agreed the results of other studies in different sea areas (Tuzhilkin and Kosarev, 2005;Zaker et al, 2007;Zavialov et al, 2022). Evaluations of salinity and temperature recorded data showed that the thermohaline structure has vertical and horizontal = ) (Kosarev, 1990;Kosarev and Yablonskaya, 1994;Tuzhilkin et al, 1997;Ibraev et al, 1998;Ibrayev, 2001;Ibrayev et al, 2001;Tuzhilkin and Kosarev, 2004;Nasimi and Ghiassi, 2006;Zounematkermani and Sabbaghyazdi, 2010;Kitazawa and Yang, 2012;Cutroneo et al, 2017;Jamshidi, 2017;Medvedev et al, 2020). The stability frequency is also called stratification frequency.…”
Section: Data Availability Statementsupporting
confidence: 90%
“…The results obtained in this research were agreed the results of other studies in different sea areas (Tuzhilkin and Kosarev, 2005;Zaker et al, 2007;Zavialov et al, 2022). Evaluations of salinity and temperature recorded data showed that the thermohaline structure has vertical and horizontal = ) (Kosarev, 1990;Kosarev and Yablonskaya, 1994;Tuzhilkin et al, 1997;Ibraev et al, 1998;Ibrayev, 2001;Ibrayev et al, 2001;Tuzhilkin and Kosarev, 2004;Nasimi and Ghiassi, 2006;Zounematkermani and Sabbaghyazdi, 2010;Kitazawa and Yang, 2012;Cutroneo et al, 2017;Jamshidi, 2017;Medvedev et al, 2020). The stability frequency is also called stratification frequency.…”
Section: Data Availability Statementsupporting
confidence: 90%
“…Ibrayev [17] developed a three-dimensional primitive equation numerical model (MESH) in spherical coordinates system with vertical array Z for simulation of water circulation in the CS. A conjunctive numerical model consisting of a 2D depth average model and a 3D pseudo compressible model in the Cartesian coordinate system was developed by Zounemat Kermani and Sabbagh Yazdi to simulate wind driven current in the CS [18]. Kitazawa and Yang (2012) simulated water circulation in the CS by means of developmet of a three dimensional numerical simulation based on a hydrodynamic ocean model (MEC) in the Cartesian coordinate system [19].…”
Section: Introductionmentioning
confidence: 99%